1999
DOI: 10.1148/radiology.212.2.r99au10453
|View full text |Cite
|
Sign up to set email alerts
|

Fecal Incontinence: Endoanal US versus Endoanal MR Imaging

Abstract: MR imaging is more accurate than US for demonstration of sphincter lesions. MR imaging provides higher spatial resolution and better inherent image contrast for lesion characterization. Endoanal MR imaging allows more precise description of the extent and structure of complex lesions and is superior for help in decisions about optimal therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
54
0
7

Year Published

1999
1999
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 144 publications
(63 citation statements)
references
References 21 publications
(19 reference statements)
2
54
0
7
Order By: Relevance
“…Unfortunately, it has only a 65% success rate. A recent study indicated that external sphincteric atrophy detectable only with endoanal MR imaging could be predictive of a poor outcome of anterior anal repair (9). In this respect, the use of endoanal MR imaging may lead to better patient selection and therefore better results.…”
Section: N Effect On Treatment Of Fecal Incontinencementioning
confidence: 99%
See 2 more Smart Citations
“…Unfortunately, it has only a 65% success rate. A recent study indicated that external sphincteric atrophy detectable only with endoanal MR imaging could be predictive of a poor outcome of anterior anal repair (9). In this respect, the use of endoanal MR imaging may lead to better patient selection and therefore better results.…”
Section: N Effect On Treatment Of Fecal Incontinencementioning
confidence: 99%
“…On coronal images, the thickness of all anal muscles may be compared; such comparison makes external sphincteric atrophy easy to detect (Fig 11). Several studies have demonstrated a good correlation between atrophy as seen at endoanal MR imaging and the findings at surgery and histopathologic investigation of the biopsy specimens (8,9). Therefore, endoanal MR imaging is of major importance in the preoperative assessment of fecal incontinence.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the assessment of perianal Crohn's disease, EUS has a 91% accuracy, comparable and complementary to MRI and evaluation under general anaesthetic 55 . EUS also has >90% sensitivity for the detection of anal sphincter defects in faecal incontinence 56 , 57 however studies comparing EUS with MRI are conflicting 58 , 59 .…”
Section: Perianal Diseasementioning
confidence: 99%
“…Zur Diagnosestellung der externen Sphinkterruptur wurde beispielsweise die endoanale MR gegenüber dem Ultraschall als besser betrachtet[12].Während andere die beiden Verfahren gleich bewerteten, wurde das MR in der Diagnostik der internen Sphinkterpathologie als das Unterlegenere bezeichnet[10]. Letztlich ergänzen sich beide Untersuchungen, und es ist am besten mit beiden vertraut zu sein.…”
unclassified